2023
DOI: 10.3389/fimmu.2023.1190699
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the autonomic cardiorespiratory activity in parturient women with severe and moderate features of preeclampsia

Elias Yojairi Pichardo-Carmona,
José Javier Reyes-Lagos,
Rosselin Gabriela Ceballos-Juárez
et al.

Abstract: BackgroundCardiorespiratory coupling (CRC) is a physiological phenomenon that reflects the mutual interaction between the cardiac and respiratory control systems. It is mainly associated with efferent vagal activity from the central autonomic network. Few studies have explored the autonomic changes of CRC in preeclampsia, a critical obstetric complication related to possible autonomic dysfunctions and inflammatory disturbances. This study examined the autonomic mechanisms of CRC in women with severe and modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Furthermore, we acknowledge the limited number of subjects. Our decision on the participant count was influenced by prior research, specifically the study by Pichardo-Carmona et al (2023) , which successfully identified autonomic differences in preeclamptic women during labor, and the work by Montalvo-Jaramillo et al (2020) that analysed fHRV in active labor. These previous studies supported the adequacy of our sample size for the exploratory objectives at hand.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, we acknowledge the limited number of subjects. Our decision on the participant count was influenced by prior research, specifically the study by Pichardo-Carmona et al (2023) , which successfully identified autonomic differences in preeclamptic women during labor, and the work by Montalvo-Jaramillo et al (2020) that analysed fHRV in active labor. These previous studies supported the adequacy of our sample size for the exploratory objectives at hand.…”
Section: Limitationsmentioning
confidence: 99%